Study of special capacity in boxers with different styles of fight - V.V. Aksutin; G.V. Korobeynikov (Physical Education of Students, 2014)
Purpose : the determination of tendency in boxer to a certain style of fight is important at all stages. Material : The special capacity in boxers with different styles of fight were studied. The special capacity and the impact force were studied by special training equipment among 23 boxers of higher qualification. The absolute and the relative strength of serial and single strikes were studied. Results : the results indicated that the absolutely impact force, the total tonnage and the relative strength of his right hand of strikes in boxers-“strongman” are more higher than in boxers with different styles. In boxers-“player” the power-hitting left-handed is more increasing for different styles. This fact indicates the presence among boxers-“player” the left-handed persons. Conclusions : the presented data are indicated about more higher of special endurance in boxers-“fastest”. This group of boxers differs from other of more higher development speed endurance